2020
DOI: 10.1155/2020/5782178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Yellow Oil Formulations 3 and 4 versus Indomethacin Solution in Patients with Symptomatic Osteoarthritis of the Knee: A Randomized Controlled Trial

Abstract: Background. Topical nonsteroidal anti-inflammatory drugs (NSAIDs) are widely prescribed for the treatment of symptomatic osteoarthritis (OA) of the knee. However, searching for alternatives such as locally available medicinal herbs to manage OA knee pain remains of clinical value. The objective of the present study was to evaluate the efficacy and safety of two yellow oil formulations in patients with OA of the knee. Methods. This prospective, randomized, single-blind, active-controlled, noninferiority study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…However, this study found that SHT extract showed good reduction in stiffness index, significantly different with day 0 and no significant difference with diclofenac. SHT extract showed different results when compared with SHT powder; in that, SHT extract showed better efficacy on stiffness reduction than SHT powder [ 5 ]. In addition, the total stiffness score of SHT extract decreased on days 14 and 28, equal to that of diclofenac.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study found that SHT extract showed good reduction in stiffness index, significantly different with day 0 and no significant difference with diclofenac. SHT extract showed different results when compared with SHT powder; in that, SHT extract showed better efficacy on stiffness reduction than SHT powder [ 5 ]. In addition, the total stiffness score of SHT extract decreased on days 14 and 28, equal to that of diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that SHT extract was more effective on OA knee patients than SHT powder. Both extract and powder of SHT showed no significant difference when compared with diclofenac [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Only symptomatical treatment of OA can be performed. Hence, analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) addressing pain and inflammation are the therapeutic options for OA 45 , 46 with adverse effects in long-term use. 47 NSAIDs are widely prescribed for the treatment of symptomatic OA of the knee.…”
Section: Oa Is So Far Untreatablementioning
confidence: 99%
“…Given the large number of people affected with osteoarthritis of the knee and societal trends in population aging and obesity [ 14 ], identifying effective and safe therapeutic options that are available in a region is viewed as a priority for sustainable development in a country [ 15 ]. In this regard, herbal medicine could be a promising approach to be employed in developing such therapeutic options [ 16 ].…”
Section: Introductionmentioning
confidence: 99%